Perutusan Tahun Baru 2003 Dekan Hal Ehwal Pelajar - Safei, Su'aidi (KUTKM, 2003)
Apart from carrying out routine activities in the list of student affairs office (HEP), all seven units of HEP has already made plans to implement several new agenda in order to establish a more intimate internal communications, simultaneously interact with other agencies, particularly other higher education institutions.